A review on silver nanoparticles focusing on applications in biomedical sector - Ankush Kumar; Vishakha; Anjana Devi; Kamal Jeet; Sanjay Kumar; Rohit Bhatia (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2022)
Considering that nanosilver-based materials have shown to have a novel, demanding, and promising properties appropriate for a variety of biological applications, silver nanoparticles (AgNPs) have evolved into one of the most researched and examined nanostructures created from nanotechnology in recent years. Silver nanoparticles (AgNPs) have been the subject of research due to their special characteristics, and they have considerable interest in medical applications such as highly excellent antimicrobial agents even without toxic effects, and industrial applications such as inkjet inks comprising well-unified dispersions of nano-sized silver particles that are useful for creating electronic circuits. Due to the remarkable activities shown by silver nanoparticles, they have been the focus of many researchers for developing new medications with less toxic effects. In this study, we have highlighted some entitled applications of silver nanoparticles. This review will be helpful for the researchers working on silver nanoparticles.